SYSTEM FACTORS ANALYSIS OF BUSINESS ENTITIES FINANCIAL PROTECTION IN UKRAINE - Batrakova, Tetyana (Journal of European Economy, 2017)
In modern conditions the radical changes of management of economic processes, that caused by development of market economy, rapid changes of internal and external factors of economic entities environment functioning, cause a threat to its financial interests, high level of financial risk, which leads to the need of improvement the concept of ensuring effective enterprise and management. The company’s ability to withstand external threats in the market environment that can lead to violations of balance in security depends on many factors, quantitative and qualitative parameters. Determination of basic classification signs of system factor: effects scale, intensity rate, impact time, scope of use, exposure time, the complexity of development, perspectives and effectiveness of influence makes possible to analyze and determine the impact of each factor on economic security of enterprise, identify the reserves of financial protection increase for proper management. Therefore, taking steps to reduce their impact is the key to successful operation of subjects on the market. The existence of effective system of financial security that will protect enterprises from threats is one of the most important conditions for smooth growth of the company and formation of positive results of its financial operation in a long- term period.